HUBUNGAN ANTARA OBESITAS DAN KEJADIAN OSTEOARTRITIS SENDI LUTUT DI POLI BEDAH TULANG RUMAH SAKIT UMUM DOKTER SOEDARSO PONTIANAK TAHUN 2013 - ., Ferdiansyah (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2015)
Background: Osteoarthritis is the most common joint disease in theworld,including Indonesia. Obesity is a risk factor that can modification tooccurance knee osteoartritis Objective: To determine the relationtionshipbetween obesity and occurrence osteoartritis of the knee in Orthopedicpolylinic of dr. Soedarso General Hospital Pontianak on 2013. Method:This research was an analytic study with cross sectional.It was conductedon Orthopedic Polyclinic with total subject were 64 peoplesÂ with chisquaretest. Results: The results obtained using the chi - square testgenerate yield p = 0.004 Conclusion: There is relationship beetweenoesity and occurrence osteoarthritis of the knee in Orthopedic polyclinic ofdr. Soedarso General Hospital Pontianak on 2013.Keyword: Osteoarthritis of the knee, obesity, Body Mass Index (BMI)